Simple model for sequential multiphoton ionization by ultraintense x rays - Li, Xiang; Boll, Rebecca; Rolles, Daniel; Rudenko, Artem (My University, 2021)
A simple model for sequential multiphoton ionization by ultraintense x rays is presented. The derived scaling of the ion yield with pulse energy quantitatively reproduces the experimental data, which shows that the ion yield increases according to the “power-law” behavior typical of multiphoton ionization, followed by saturation at high pulse energies. The calculated average time interval between ionizations for producing ions at a certain charge state is found to be proportional to the pulse duration and independent of all other x-ray pulse parameters. This agrees with previous studies where the kinetic energy of fragment ions with a given charge state produced by the intense x-ray ionization of molecules was found to be independent of the pulse energy, but to increase with a smaller pulse duration due to the smaller time interval between ionizations.